Integrasi Kecerdasan Buatan Dalam Praktik Dan Kehidupan Pemuda Kristen - Yosefo Gule (STT Pelita Dunia, 2026)
The development of artificial intelligence (AI) has impacted various aspects of human life, including religion. This study aims to explore how AI integration influences the spiritual practices and social lives of Christian youth, particularly in Bible study, online worship, and digital communities. A literature review methodology was employed, analyzing relevant academic literature and empirical reports on AI, digital Christianity, and Christian youth dynamics. The findings show that AI provides significant opportunities for supporting the spiritual growth of Christian youth through improved information accessibility, personalized worship experiences, and flexibility in engaging with spiritual life. However, the study also highlights challenges such as reduced physical community interaction, the risk of faith individualization, and ethical concerns regarding spiritual authority and religious experience authenticity. The research underscores that AI integration should be guided by theological discernment rooted in biblical principles, an understanding of the Imago Dei, and digital ethics awareness. Thus, AI can become a strategic partner in shaping a tech-savvy yet faith-driven generation of Christian youth, grounded in essential values. This study contributes both conceptually and practically to the development of relevant Christian ministry approaches in the digital age.